Contributions to the theory of nonlinear oscillations. - Antosiewicz, H.; Lefschetz, S. (Annals of mathematics studies ;, 1958)
The description for this book, Contributions to the Theory of Nonlinear Oscillations (AM-41), Volume IV, will be forthcoming.